Socio-Economic Drivers of Sustainable Consumption Behaviour in Rural and Urban Areas: A Partial Least Squares Multi-Group Analysis (Journal of Asian Development Studies, 2025)
Sustainable consumption behaviour can address environmental, social, and economic problems created by unsustainable consumption behaviour, whereas socio-economic factors are crucial factors which influence human consumption behaviour. Therefore, this study conducted a comparative analysis of urban-rural Khyber Pakhtunkhwa regarding the effects of socio-economic factors on sustainable consumption behaviour. The Krejcie and Morgan method was used to determine the sample size, and the multistage cluster sampling technique was used to form the whole sample from the target population. Data from sampled respondents were collected through self-administered questionnaires. Partial Least Squares Multigroup Analysis (PLS-MA) was used to analyse the data. The findings of this study demonstrate that all socio-economic factors included in this study, except Gender, significantly affect sustainable consumption behavior. The coefficients of Gender (β=0.15, P